As shopkeeper X give 1000 back to shopkeeper Y. It is whole loss. Also, he gave 200(product) to Man(M).

Loss to shopkeeper X is 200(Product given to Man M)+ 1000 (Given back to shopkeeper Y) => 1200

As shopkeeper X give 1000 back to shopkeeper Y. It is whole loss. Also, he gave 200(product) to Man(M).

Loss to shopkeeper X is 200(Product given to Man M)+ 1000 (Given back to shopkeeper Y) => 1200

X still has the 200/- for the product. So the loss is 1200 - 200 = 1000/-.

Think it this way:

X has 1000/- initially, 200/- in form of the product and 800/- as cash.

After sale he has 1000/- in form of cash.

Then Y asks for 1000/- from X.

X now has 1000 - 1000 = 0/-.

Loss = final - initial = 0 - 1000 = -1000/-

since the note is wrong from the beginning he had to lose (200 to customer and 800 to Y ) all of which is completely Y’s money

1000 0f Y’s =200 to customer + 800 change

so return =1000